Whey Tahu sebagai Penghasil Biolektrisitas pada Sistem Microbial Fuel Cell dengan Lactobacillus Plantarum - Ismawati, Nur; Aminin, Agustina L. N.; Suyati, Linda (JURNAL SAINS DAN MATEMATIKA, 2015)
Bioelectricity of soy whey in Microbial Fuel Cell system with Lactobacillus plantarum has been performed. This study aims to determine the capacity of soy whey as a substrate in the MFC system and determine the influence of the speed of agitation against potential difference generated. The potential difference compared to different substrates, namely soy whey, glucose and lactose. Determination of the potential difference in speed variation agitation performed with variations 30, 60, 90, 125 and 250 rpm. The potential difference at the maximum voltage variation of the substrate obtained by soy whey by 33.3 mV / 100 mL at the 15th hour, whereas glucose and lactose reaches the maximum potential difference at the 12th hour with a relatively similar value. Agitation speed that generates the highest potential difference in soy whey substrate was obtained at 90 rpm with maximum potential difference of 63.1 mV / 100mL at the 14th hour.